Study on the mechanism behind lncRNA MEG3 affecting clear cell renal cell carcinoma by regulating miR‐7/RASL11B signaling. Issue 12 (3rd July 2018) - He, Hongchao; Dai, Jun; Zhuo, Ran; Zhao, Juping; Wang, Haofei; Sun, Fukang; Zhu, Yu; Xu, Danfeng
Abstract : The goal of this research was to study the relationships between maternally expressed gene 3 (MEG3), microRNA‐7 (miR‐7), and RASL11B, and explore their influence on the progression of clear cell renal cell carcinoma (CCRCC). Microarray analysis was conducted using the data provided by The Cancer Genome Atlas. The expression levels of MEG3 and miR‐7 in CCRCC and adjacent tissue samples were ascertained by quantitative real‐time polymerase chain reaction (qRT‐PCR). The cell proliferation activity was unmasked by 3‐(4, 5‐dimethylthiazol‐2‐yl)‐2, 5‐diphenyltetrazolium bromide assay, and cell apoptosis and cell cycle were investigated by flow cytometry. A dual luciferase reporter assay was used to verify target relationships. Wound healing assay and transwell assay were used to detect cell migration and invasion ability. Decreased MEG3 expression was observed in CCRCC tissues and cells. Overexpression of MEG3 accelerated apoptosis; inhibited cell proliferation, migration and invasion; and induced G0/G1 phase cell cycle arrest in CCRCC. MiR‐7, directly binding to MEG3, was overexpressed in the CCRCC tissues and could inhibit the apoptosis and promote the migration and invasion of CCRCC cells. RASL11B, lowly expressed in CCRCC, was a target of miR‐7. After the overexpression of RASL11B, G0/G1 phase cell cycle arrest was induced; cell apoptosis was promoted; and the proliferation, invasion, and migration of CCRCC cells were inhibited. MEG3 could up‐regulate RASL11B to inhibit the cell proliferation, invasion, and migration; induce G0/G1 cell cycle arrest; and promote cell apoptosis by suppressing miR‐7 in CCRCC. Abstract : The goal of this study was to study the relationships between maternally expressed gene 3 (MEG3), microRNA‐7 (miR‐7), and RASL11B, and explore their influence on the progression of clear cell renal cell carcinoma (CCRCC). MEG3 could up‐regulate RASL11B to inhibit cell proliferation, invasion and migration; induce G0/G1 cell cycle arrest; and promote cell apoptosis by suppressing miR‐7 in CCRCC.